Synthesis of new alkyl derivatives of N(1)-(2’-bromo-1’,1’-difluoro-2’-chloroethyl)uracil with potential antitumor activity - O. V. Velchynska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
The most common ways of their chemical modification are used namely, electrophilic and nucleophilic substitution reactions during the purposeful search for active substances among pyrimidines with aromatic properties. Antimetabolites of pyrimidine metabolism are one of the objects of the most successful and promising areas of search for highly effective antitumor drugs.